Carbon nanotube-based flexible electrothermal film heaters with a high heating rate. Issue 6 (6th June 2018) - Jia, Song-Lin; Geng, Hong-Zhang; Wang, Luda; Tian, Ying; Xu, Chun-Xia; Shi, Pei-Pei; Gu, Ze-Zeng; Yuan, Xue-Shuang; Jing, Li-Chao; Guo, Zhi-Ying; Kong, Jing
Abstract : High-performance, flexible film heaters with carbon nanotube transparent conducting films are easily fabricated by both a rod-coating method and a spraying method. The main conclusion we have reached is that the film demonstrates a heating rate of 6.1°C s −1 at 35 V and sheet resistance as low as 94.7 Ω sq −1 with 72.04% optical transmittance at a wavelength of 550 nm by the spraying method after a series of post-treatment processes with acid and distilled water. Then, we adopt a mathematical method of nonlinear fitting to simulate the collected experimental data and the functions effectively. Furthermore, through analysis of the formula, the correlation between temperature and time is well explained. Therefore, carbon nanotube-based, flexible, transparent heaters exhibit high electrothermal performance and are expected to find different applications, e.g. various functional devices such as heating materials, heatable smart windows or dining tables.